ANALYSIS OF CONSTRUCTION NAZI STATE: THE UNIFICATION PROCESS IN SOCIAL AND ECONOMIC POLICY - Кеворкян, К.Е. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The paper investigates the process of nation building of Nazi Germany in 1933-1939 years. Particular attention is paid to the policy of unification of the spiritual sphere, advocacy component of social and economic policy of the German state, and the analysis of specific social projects of the Nazi regime and its propaganda potential.